Patient satisfaction in an acute medicine department in Morocco - Soufi Mehdi; Ahid Samir; Himmich Salma; Belayachi Jihane; Soufi Ghizlane; Zekraoui Aicha; Abouqal Redouane (BMC, 2010)
Abstract Background Patients' satisfaction is an important indicator for quality of care. Measuring healthcare quality and improving patient satisfaction have become increasingly prevalent, especially among healthcare providers and purchasers of healthcare. This is mainly due to the fact that consumers are becoming increasingly more knowledgeable about healthcare. No studies of inpatients' satisfaction with hospital care have been conducted in Morocco. The first objective of the present study was to confirm the reliability and validity of the Arabic version of the EQS-H (Echelle de Qualité des Soins en Hospitalisation). The second objective was to evaluate patient satisfaction in an acute medicine department in Morocco by using the EQS-H questionnaire; and also to assess the influence of certain demographics, socioeconomics, and health characteristics in patient satisfaction. Methods it was a patient survey conducted in an acute medicine department of a Moroccan University Hospital. We surveyed their socio demographic status, and health characteristics at admission. We performed structured face to face interviews with patients who were discharged from hospital. The core of the EQS-H questionnaire was translated to Arabic, adapted to the present setting, and then used to measure patient satisfaction with quality of care. The internal consistency of the EQS-H scale was assessed by Chronbach's coefficient alpha. Validity was assessed by factor analysis. Factors influencing inpatients' satisfaction were identified using multiple linear regression. Results The Arabic version of EQS-H demonstrated an excellent internal consistency for the two dimensions studied (0.889 for 'quality of medical information' (MI) and 0.906 for 'Relationship with staff and daily routine' (RS)). The principal component analysis confirmed the bidimensional structure of the questionnaire and explained 60% of the total variance. In the univariate analysis, urban residence, higher income, better perceived health status compared to admission, better perceived health status compared to people of the same age, and satisfaction with life in general were related to MI dimension; Otherwise, mal gender, urban residence, higher income, staying in double room, better perceived health status compared to admission, and satisfaction with life in general were related to RS dimension. The multiple linear regression showed that four independent variables were associated with higher satisfaction in MI: More than 2 prior hospitalizations, a longer length of stay (10-14 days) (P = 0.002), staying in double room (P = 0.022), and better perceived health status compared to admission (P = 0.036). Three independent variables were associated with higher satisfaction in RS: a longer length of stay (10-14 days) (P = 0.017), better perceived health status compared to admission day (P = 0.013), and satisfaction with life in general (P = 0.006). Conclusions Our current data assessing patient satisfaction with acute health care by the Arabic version of the EQS-H showed that the satisfaction rate was average on MI dimension; and good on RS dimension of the questionnaire. The majority of participants were satisfied with the overall care. Demographic, socioeconomic, and health characteristics may influence in-patients satisfaction in Morocco, a low/middle income country. An appreciation and understanding of these factors is essential to develop socio culturally appropriate interventions in order to improve satisfaction of patients.